Dianthus superbus fructus suppresses airway inflammation by downregulating of inducible nitric oxide synthase in an ovalbumin-induced murine model of asthma - Shin In-Sik; Lee Mee-Young; Ha Hyekyung; Jeon Woo-Young; Seo Chang-Seob; Shin Hyeun-Kyoo (BMC, 2012)
Abstract Background Dianthus superbus has long been used as a herbal medicine in Asia and as an anti-inflammatory agent. In this study, we evaluated the anti-inflammatory effects of Dianthus superbus fructus ethanolic extract (DSE) on Th2-type cytokines, eosinophil infiltration, and other factors in an ovalbumin (OVA)-induced murine asthma model. To study the possible mechanism of the anti-inflammatory effect of DSE, we also evaluated the expression of inducible nitric oxide synthase (iNOS) in the respiratory tract. Methods Mice were sensitized on days 0 and 14 by intraperitoneal injection of OVA. On days 21, 22 and 23 after initial sensitization, mice received an airway challenge with OVA for 1 h using an ultrasonic nebulizer. DSE was applied 1 h prior to OVA challenge. Mice were administered DSE orally at doses of 100 mg/kg or 200 mg/kg once daily from day 18 to 23. Bronchoalveolar lavage fluid (BALF) was collected 48 h after the final OVA challenge. Levels of interleukin (IL)-4, IL-13 and eotaxin in BALF were measured using enzyme-linked immunosorbent assays (ELISAs). Lung tissue sections were stained with hematoxylin and eosin for assessment of cell infiltration and mucus production with periodic acid shift staining, in conjunction with ELISA and western blot analyses for iNOS expression. Results DSE significantly reduced the levels of IL-4, IL-13, eotaxin, and immunoglobulin (Ig) E, number of inflammatory cells in BALF, and inflammatory cell infiltration and mucus production in the respiratory tract. DSE also attenuated the overexpression of iNOS protein induced by OVA challenge. Conclusion Our results suggest that DSE effectively protects against allergic airway inflammation by downregulating of iNOS expression and that DSE has potential as a therapeutic agent for allergic asthma.